Homogeneous catalysis for unreactive bond activation - Shi, Zhangjie, 1974- (Hoboken, New Jersey : Wiley, 2014)
"This book offers a comprehensive overview of different catalytic reactions applied to the activation of chemical bonds. Each of the seven chapters cover key C-X classes where carbon is combined with another element: chlorine, fluorine, nitrogen, sulfur, oxygen, hydrogen, and carbon"--
6.2 Mechanism of C-H Cleavage6.3 Directed C-H Oxidation; 6.4 Hydroarylation; 6.5 Direct Arylation; 6.6 Carbonylation; 6.7 Hydroacylation; 6.8 Alkane Dehydrogenation; 6.9 Borylation and Silylation; 6.10 Summary and Outlook; References; Chapter 7: Catalysis in C-C Activation; 7.1 Introduction: Importance and Challenges in C-C Activation; 7.2 C-C Activation of Strained Molecules; 7.3 C-C Activation of Unstrained Molecules; 7.4 Summary and Perspective; References; Index; End User License Agreement
Machine generated contents note: Preface Contributor List Chapter 1: Catalysis in C-Cl Activation Zhong-Xia Wang and Wang-Jun Guo Chapter 2: Homogeneous Transition-metal Catalyzed C-F Activation Shang-Dong Yang Chapter 3: Homogeneous Transition-metal Catalzyed C-N Activation Xiao-Bing Wan Chapter 4: Catalytic Carbon-Sulfur Bond Activation and Transformations Zhengkun Yu Chapter 5: Homogeneous Transition-Metal-Catalzyed C-O Bond Activation Da-Gang Yu, Shuang Luo, Fei Zhao, and Zhang-Jie Shi Chapter 6: Homogeneous Transition-Metal-Catalyzed C-H Bond Functionalization Bi-Jie Li and Zhang-Jie Shi Chapter 7: Catalysis in C-C Activation Hu Li and Zhang-Jie Shi.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Homogeneous catalysis; Carbon, Activated; Chemical bonds; SCIENCE -- Chemistry -- Organic; SCIENCE -- Chemistry -- Physical & Theoretical; SCIENCE -- Chemistry -- General; Carbon, Activated; Chemical bonds; Homogeneous catalysis; Electronic books; Electronic books